Biocatalytic Friedel–Crafts Acylation and Fries Reaction. Issue 26 (23rd May 2017) - Schmidt, Nina G.; Pavkov‐Keller, Tea; Richter, Nina; Wiltschi, Birgit; Gruber, Karl; Kroutil, Wolfgang
Abstract: The Friedel–Crafts acylation is commonly used for the synthesis of aryl ketones, and a biocatalytic version, which may benefit from the chemo‐ and regioselectivity of enzymes, has not yet been introduced. Described here is a bacterial acyltransferase which can catalyze Friedel–Crafts C‐acylation of phenolic substrates in buffer without the need of CoA‐activated reagents. Conversions reach up to >99 %, and various C‐ or O‐acyl donors, such as DAPG or isopropenyl acetate, are accepted by this enzyme. Furthermore the enzyme enables a Fries rearrangement‐like reaction of resorcinol derivatives. These findings open an avenue for the development of alternative and selective C−C bond formation methods. Abstract : Order up on Fries : The biocatalytic acylation of resorcinol substrates, catalyzed by an acyltransferase, leads to C‐acylated products. The Friedel–Crafts bio‐C‐acylation allows use of simple activated esters, such as isopropenyl acetate, as an acyl source. Additionally the enzyme enables a Fries rearrangement‐like reaction.